hGATA1 Under the Control of a μLCR/β-Globin Promoter Rescues the Erythroid but Not the Megakaryocytic Phenotype Induced by the Gata1low Mutation in Mice - Martelli, Fabrizio; Verachi, Paola; Zingariello, Maria; Mazzarini, Maria; Vannucchi, Alessandro M.; Lonetti, Annalisa; Bacci, Barbara; Sarli, Giuseppe; Migliaccio, Anna Rita (Frontiers in Genetics, 2021)
The phenotype of mice carrying the Gata1low mutation that decreases expression of Gata1 in erythroid cells and megakaryocytes, includes anemia, thrombocytopenia, hematopoietic failure in bone marrow and development of extramedullary hematopoiesis in spleen. With age, these mice develop myelofibrosis, a disease sustained by alterations in stem/progenitor cells and megakaryocytes. This study analyzed the capacity of hGATA1 driven by a μLCR/β-globin promoter to rescue the phenotype induced by the Gata1low mutation in mice. Double hGATA1/Gata1low/0 mice were viable at birth with hematocrits greater than those of their Gata1low/0 littermates but platelet counts remained lower than normal. hGATA1 mRNA was expressed by progenitor and erythroid cells from double mutant mice but not by megakaryocytes analyzed in parallel. The erythroid cells from hGATA1/Gata1low/0 mice expressed greater levels of GATA1 protein and of α- and β-globin mRNA than cells from Gata1low/0 littermates and a reduced number of them was in apoptosis. By contrast, hGATA1/Gata1low/0 megakaryocytes expressed barely detectable levels of GATA1 and their expression of acetylcholinesterase, Von Willebrand factor and platelet factor 4 as well as their morphology remained altered. In comparison with Gata1+/0 littermates, Gata1low/0 mice contained significantly lower total and progenitor cell numbers in bone marrow while the number of these cells in spleen was greater than normal. The presence of hGATA1 greatly increased the total cell number in the bone marrow of Gata1low/0 mice and, although did not affect the total cell number of the spleen which remained greater than normal, it reduced the frequency of progenitor cells in this organ. The ability of hGATA1 to rescue the hematopoietic functions of the bone marrow of the double mutants was confirmed by the observation that these mice survive well splenectomy and did not develop myelofibrosis with age. These results indicate that hGATA1 under the control of µLCR/β-globin promoter is expressed in adult progenitors and erythroid cells but not in megakaryocytes rescuing the erythroid but not the megakaryocyte defect induced by the Gata1low/0 mutation.